The R882H DNMT3A hot spot mutation stabilizes the formation of large DNMT3A oligomers with low DNA methyltransferase activity - Nguyen, Tuong-Vi; Yao, Shihua; Wang, Yahong; Rolfe, Alan; Selvaraj, Anand; Darman, Rachel; Ke, Jiyuan; Warmuth, Markus; Smith, Peter G.; Larsen, Nicholas A.; Yu, Lihua; Zhu, Ping; et al. (The Journal of biological chemistry, 2019)
DNMT3A (DNA methyltransferase 3A) is a de novo DNA methyltransferase responsible for establishing CpG methylation patterns within the genome. DNMT3A activity is essential for normal development, and its dysfunction has been linked to developmental disorders and cancer. DNMT3A is frequently mutated in myeloid malignancies with the majority of mutations occurring at Arg-882, where R882H mutations are most frequent. The R882H mutation causes a reduction in DNA methyltransferase activity and hypomethylation at differentially-methylated regions within the genome, ultimately preventing hematopoietic stem cell differentiation and leading to leukemogenesis. Although the means by which the R882H DNMT3A mutation reduces enzymatic activity has been the subject of several studies, the precise mechanism by which this occurs has been elusive. Herein, we demonstrate that in the context of the full-length DNMT3A protein, the R882H mutation stabilizes the formation of large oligomeric DNMT3A species to reduce the overall DNA methyltransferase activity of the mutant protein as well as the WT–R882H complex in a dominant-negative manner. This shift in the DNMT3A oligomeric equilibrium and the resulting reduced enzymatic activity can be partially rescued in the presence of oligomer-disrupting DNMT3L, as well as DNMT3A point mutations along the oligomer-forming interface of the catalytic domain. In addition to modulating the oligomeric state of DNMT3A, the R882H mutation also leads to a DNA-binding defect, which may further reduce enzymatic activity. These findings provide a mechanistic explanation for the observed loss of DNMT3A activity associated with the R882H hot spot mutation in cancer.